2021
DOI: 10.7759/cureus.20370
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Male Students Perception Towards Their Weight, Almethnab Town, Qassim, Saudi Arabia

Abstract: To determine the perception of Almethnab town secondary school male students towards their body weights. MethodologyWe surveyed male secondary school students in Almethnab town in Qassim using a self-administered questionnaire and weighing/height scale. All of the four secondary schools were targeted. The calculated sample size was 256 students. A stratified cluster sampling technique was used to select research participants. Body mass index (BMI) was calculated and interpreted using web-based CDC childhood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This is similar to the findings of a study by AsSaigal et al that measured the body weight perceptions of 270 male secondary school students in the Qassim region of Saudi Arabia. They found that 35% perceived their weight incorrectly, with 18.4% of overweight and obese students perceiving their weight as normal, 53% of the underweight students also perceiving their weight as normal, and 20% of the normal-weight students perceiving themselves as overweight [21].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the findings of a study by AsSaigal et al that measured the body weight perceptions of 270 male secondary school students in the Qassim region of Saudi Arabia. They found that 35% perceived their weight incorrectly, with 18.4% of overweight and obese students perceiving their weight as normal, 53% of the underweight students also perceiving their weight as normal, and 20% of the normal-weight students perceiving themselves as overweight [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also reported among a Mediterranean adult population [ 21 ]. In a small local study, 18.4% of overweight or obese young males reported their weight as appropriate [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the 21st century, there has been a growing focus on studying school environments and their connection to student well-being [ 6 ]. The school environment is recognized as an influential factor in shaping students’ eating behaviors, enabling them to make healthier food choices and lower their body mass index (BMI) [ 7 ]. Additionally, the physical activity of students is influenced by the school’s structure, such as the availability of playgrounds and access to play facilities, which play a crucial role in promoting physical activity [ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%